Asthma in United States olympic athletes who participated in the 1998 olympic winter games - Weiler, J. M.; Ryan, E. J. (Journal of Allergy and Clinical Immunology, 2000)
BACKGROUND: About one of every 5 athletes who participated in the 1996 Summer Olympic Games in Atlanta had a past history of asthma, had symptoms that suggested asthma, or took asthma medications. No previous study has determined the prevalence of asthma in all US athletes who participated in an Olympic Winter Games. OBJECTIVES: We sought to determine how many US athletes who participated in the 1998 Olympic Winter Games had a past history of asthma, had symptoms that suggested asthma, or indicated taking a medication used to treat asthma. METHODS: We evaluated responses to questions that asked about allergic and respiratory diseases in the United States Olympic Committee Medical History Questionnaire that was completed by all 196 athletes who represented the United States at the 1998 Olympic Winter Games in Nagano, Japan. RESULTS: Forty-three (21.9%) of the 196 athletes had a previous diagnosis of asthma, and 36 (18. 4%) recorded use of an asthma medication at some time in the past. Forty-four (22.4%) reported use of an asthma medication, a diagnosis of asthma, or both (our basis for the diagnosis of asthma). Thirty-four (17.4%) of the athletes were currently taking an asthma medication at the time that they completed the questionnaire or indicated that they took these medications on a permanent or semipermanent basis and were considered to have active asthma. Athletes who participated in Nordic combined, cross-country, and short track events had the highest prevalence of having been told that they had asthma or had taken an asthma medication in the past (60.7%) in contrast with only one (2.8%) of the 36 athletes who participated in bobsled, biathlon, luge, and ski jumping. Eighteen (24%) of 75 athletes who participated in alpine, long track, figure skating, snow boarding, and curling had a previous diagnosis of asthma or recorded use of an asthma medication. CONCLUSIONS: We conclude that asthma appeared to have been more common in athletes who participated in the 1998 Winter Games than in athletes who participated in either the 1996 or 1984 Summer Games. Clearly, asthma rates vary widely among sports. This suggests that the environment in which exercise is performed is important in leading to a decrease in the amount of exercise required to trigger asthma and perhaps in causing injury to the airways.